Comparison of the genomes of two Xanthomonas pathogens with differing host specificities - da Silva, ACR; Ferro, J. A.; Reinach, F. C.; Farah, C. S.; Furlan, L. R.; Quaggio, R. B.; Monteiro-Vitorello, C. B.; Van Sluys, M. A.; Almeida, N. F.; Alves, LMC; do Amaral, A. M.; Bertolini, M. C.; et al. (Nature Publishing Group, 2002)
The genus Xanthomonas is a diverse and economically important group of bacterial phytopathogens, belonging to the gamma-subdivision of the Proteobacteria. Xanthomonas axonopodis pv. citri (Xac) causes citrus canker, which affects most commercial citrus cultivars, resulting in significant losses worldwide. Symptoms include canker lesions, leading to abscission of fruit and leaves and general tree decline(1). Xanthomonas campestris pv. campestris (Xcc) causes black rot, which affects crucifers such as Brassica and Arabidopsis. Symptoms include marginal leaf chlorosis and darkening of vascular tissue, accompanied by extensive wilting and necrosis(2). Xanthomonas campestris pv. campestris is grown commercially to produce the exopolysaccharide xanthan gum, which is used as a viscosifying and stabilizing agent in many industries(3). Here we report and compare the complete genome sequences of Xac and Xcc. Their distinct disease phenotypes and host ranges belie a high degree of similarity at the genomic level. More than 80% of genes are shared, and gene order is conserved along most of their respective chromosomes. We identified several groups of strain-specific genes, and on the basis of these groups we propose mechanisms that may explain the differing host specificities and pathogenic processes.